Damage to the wood of forest species caused by the debarking of Pallas´s squirrel introduced into Argentina - PEDREIRA, Paula A.; PENON, Eduardo A.; GOZZI, A. Cecilia; PENON-SOBERO, Nicolás; BORGNIA, Mariela (Forest Systems, 2023)
Aim of study: Pallas´s squirrel (Callosciurus erythraeus) is a harmful and generalist invasive mammal species that causes different problems in the forestry sector. The aim of this study was to evaluate the damage on the wood in three commercial tree species in Argentina, Eucalyptus dunnii, Populus deltoides and Pinus elliottii, due to debarking caused by this squirrel species.Area of study: ¨Liebres Fue¨ forest plantation, located in Luján District (Province of Buenos Aires, Argentina).Material and methods: We analyzed affected tissues and internal defects of wood associated with debarking signs. We randomly collected 74 stems of the three forest species with (N=62) and without debarking (N=12) between October 2016 and December 2017. Transversal cuttings (N=37) and longitudinal cuttings (N=37) of the stems were analyzed.Main results: The defects inside the wood related to the damage due to the debarking caused by Pallas´s squirrels are described. All the damaged samples presented affected wood tissues, with unfavorable healing forming ribbed cracks and ram`s horn scars and/or presence of some internal defect (crack, crack with abnormal coloration, crack with kino/resin or crack with bark included). None of the damaged pieces, according to the rules of visual classification of sawn woods, showed the highest quality grade (Premium).Research highlight: Pallas´s squirrel action causes wounds on the trees, leading to different responses by the trees that are transferred internally, showing abnormalities in the wood which diminish its value from a commercial point of view.